Recording Obligatory Cortical Auditory Evoked Potentials in Infants: Quantitative Information on Feasibility and Parent Acceptability. Issue 3 (May 2020) - Munro, Kevin J.; Purdy, Suzanne C.; Uus, Kai; Visram, Anisa; Ward, Rachel; Bruce, Iain A.; Marsden, Antonia; Stone, Michael A.; Van Dun, Bram
Abstract : Objectives: With the advent of newborn hearing screening and early intervention, there is a growing interest in using supra-threshold obligatory cortical auditory evoked potentials (CAEPs) to complement established pediatric clinical test procedures. The aim of this study was to assess the feasibility, and parent acceptability, of recording infant CAEPs. Design: Typically developing infants (n = 104) who had passed newborn hearing screening and whose parents expressed no hearing concerns were recruited. Testing was not possible in 6 infants, leaving 98, age range 5 to 39 weeks (mean age = 21.9, SD = 9.4). Three short duration speech-like stimuli (/m/, /g/, /t/) were presented at 65 dB SPL via a loudspeaker at 0° azimuth. Three criteria were used to assess clinical feasibility: (i) median test duration <30 min, (ii) >90% completion rate in a single test session, and (iii) >90% response detection for each stimulus. We also recorded response amplitude, latency, and CAEP signal to noise ratio. Response amplitudes and residual noise levels were compared for Fpz (n = 56) and Cz (n = 42) noninverting electrode locations. Parental acceptability was based on an 8-item questionnaire (7-point scale, 1 being best). In addition, we explored the patient experience in semistructured telephone interviews with seven families. Results: The median time taken to complete 2 runs for 3 stimuli, including preparation, was 27 min (range 17 to 59 min). Of the 104 infants, 98 (94%) were in an appropriate behavioral state for testing. A further 7 became restless during testing and their results were classified as "inconclusive." In the remaining 91 infants, CAEPs were detected in every case with normal bilateral tympanograms. Detection of CAEPs in response to /m/, /g/, and /t/ in these individuals was 86%, 100%, and 92%, respectively. Residual noise levels and CAEP amplitudes were higher for Cz electrode recordings. Mean scores on the acceptability questionnaire ranged from 1.1 to 2.6. Analysis of interviews indicated that parents found CAEP testing to be a positive experience and recognized the benefit of having an assessment procedure that uses conversational level speech stimuli. Conclusions: Test duration, completion rates, and response detection rates met (or were close to) our feasibility targets, and parent acceptability was high. CAEPs have the potential to supplement existing practice in 3- to 9-month olds. Abstract : Supplemental Digital Content is available in the text.